A new synthetic toll-like receptor 1/2 ligand is an efficient adjuvant for peptide vaccination in a human volunteer. Issue 1 (15th November 2019) - Rammensee, Hans-Georg; Wiesmüller, Karl-Heinz; Chandran, P. Anoop; Zelba, Henning; Rusch, Elisa; Gouttefangeas, Cécile; Kowalewski, Daniel J.; Di Marco, Moreno; Haen, Sebastian P.; Walz, Juliane S.; Gloria, Yamel Cardona; Bödder, Johanna; et al.
Abstract : Background: We previously showed that the bacterial lipopeptide Pam3 Cys-Ser-Ser, meanwhile established as a toll-like receptor (TLR) 1/2 ligand, acts as a strong adjuvant for the induction of virus specific CD8 + T cells in mice, when covalently coupled to a synthetic peptide. Case presentation: We now designed a new water-soluble synthetic Pam3 Cys-derivative, named XS15 and characterized it in vitro by a TLR2 NF-κB luciferase reporter assay. Further, the capacity of XS15 to activate immune cells and stimulate peptide-specific CD8 + T and NK cells by 6-sulfo LacNAc + monocytes was assessed by flow cytometry as well as cytokine induction using immunoassays. The induction of a functional immune response after vaccination of a volunteer with viral peptides was assessed by ELISpot assay and flow cytometry in peripheral blood cells and infiltrating cells at the vaccination site, as well as by immunohistochemistry and imaging. XS15 induced strong ex vivo CD8 + and TH 1 CD4 + responses in a human volunteer upon a single injection of XS15 mixed to uncoupled peptides in a water-in-oil emulsion (Montanide™ ISA51 VG). A granuloma formed locally at the injection site containing highly activated functional CD4 + and CD8 + effector memory T cells. The total number of vaccine peptide-specific functional T cells was experimentally assessed and estimated to be 3.0 × 10 5 in the granuloma and 20.5 × 10 6 in peripheral blood. Conclusion: Thus, in one volunteer we show a granuloma forming by peptides combined with an efficient adjuvant in a water-in-oil-emulsion, inducing antigen specific T cells detectable in circulation and at the vaccination site, after one single vaccination only. The ex vivo T cell responses in peripheral blood were detectable for more than one year and could be strongly boosted by a second vaccination. Hence, XS15 is a promising adjuvant candidate for peptide vaccination, in particular for tumor peptide vaccines in a personalized setting.